Role of Television Advertising and its Effect on the Living Habits of Rural Consumers - Sukhmani; Hundal, B. S. (Prabandhan: Indian Journal of Management, 2011)
The rural market of India is fascinating and challenging at the same time. It offers large scope on account of its sheer size and potential. Even a gradual growth pushes up the sales of a product substantially, in view of the huge base. The market pioneers are getting rewarded by capturing the rural markets. Simultaneously, due to the problems and hurdles posed by rural markets, the firms have to directly encounter them and put in a great deal of effort to get a sizeable share of the market. They need to recognize that rural market is a developing market. The perception of the rural masses regarding TV advertising needs to be studied to penetrate in rural markets. It is often said that markets are made, not found. This is especially true of the rural market of India. It is a market meant for the truly creative marketers.